Feasibility of Metatranscriptome Analysis from Infant Gut Microbiota: Adaptation to Solid Foods Results in Increased Activity of Firmicutes at Six Months. (24th August 2017) - Hugenholtz, Floor; Ritari, Jarmo; Nylund, Lotta; Davids, Mark; Satokari, Reetta; de Vos, Willem M.
Abstract : Newborns are rapidly colonized by microbes and their intestinal tracts contain highly dynamic and rapidly developing microbial communities in the first months of life. In this study, we describe the feasibility of isolating mRNA from rapidly processed faecal samples and applying deep RNA-Seq analysis to provide insight into the active contributors of the microbial community in early life. Specific attention is given to the impact of removing rRNA from the mRNA on the phylogenetic and transcriptional profiling and its analysis depth. A breastfed baby was followed in the first six months of life during adaptation to solid food, dairy products, and formula. It was found that, in the weaning period, the total transcriptional activity of Actinobacteria, mainly represented by Bifidobacterium, decreased while that of Firmicutes increased over time. Moreover, Firmicutes and Actinobacteria, including the canonical Bifidobacteria as well as Collinsella, were found to be important contributors to carbohydrate fermentation and vitamin biosynthesis in the infant intestine. Finally, the expression of Lactobacillus rhamnosus -like genes was detected, likely following transfer from the mother who consumed L. rhamnosus GG. The study indicates that metatranscriptome analysis of the infant gut microbiota is feasible on infant stool samples and can be used to provide insight into the core activities of the developing community.